2015
DOI: 10.1016/j.hrmr.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing intelligence in assessment: The next step

Abstract: a r t i c l e i n f o a b s t r a c tIntelligence theory and assessment in HR and I/O contexts are unlikely to make major advancements when intelligence continues to be treated as a decontextualized set of skills. Models of cognitive style, situated cognition, and practical intelligence present a more contextualized view of intelligence, but are either too broad or too embedded in context to guide HR and I/O assessment.We propose a new model that draws a closer link between cognition and context; the model bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…(2015) found that emotional intelligence has a positive effect on social-mental factors of human resources. Further studies show that emotional intelligence has a great impact on organizations and motivating human activity (Agnello, Ryan & Yusko, 2015;Brouwers & Vijver, 2015;Schneider & Newman, 2015;Fagan & Ployhart, 2015;Scherbaum & Goldstein, 2015). It means that EI is highly significant in the development of human potential, teamwork, effective leadership, stress reduction, creativity and innovation (Chopra & Kanji, 2010).…”
Section: Talent Management and Emotional Intelligencementioning
confidence: 99%
“…(2015) found that emotional intelligence has a positive effect on social-mental factors of human resources. Further studies show that emotional intelligence has a great impact on organizations and motivating human activity (Agnello, Ryan & Yusko, 2015;Brouwers & Vijver, 2015;Schneider & Newman, 2015;Fagan & Ployhart, 2015;Scherbaum & Goldstein, 2015). It means that EI is highly significant in the development of human potential, teamwork, effective leadership, stress reduction, creativity and innovation (Chopra & Kanji, 2010).…”
Section: Talent Management and Emotional Intelligencementioning
confidence: 99%
“…In spite of the fact that general cognitive ability has been shown to predict workplace performance, there continues to be a gap between cognitive ability measured in a relatively sterile environment and observed application of that ability in solving everyday problems in the workplace (Becker et al, 2015; Brouwers & van de Vijver, 2015). This gap suggests that situational factors, such as emotion, task requirements, and so forth, may impact the application of cognitive functioning in the workplace.…”
Section: Future Research Applications In Organizational Behaviormentioning
confidence: 99%
“…We employed features of the natural environment of the Kharwar to design two sets of parallel tasks in which related processes are required for a successful completion of parallel measures, but in which the domain of application of these processes are more similar to typical school tasks or more to local tasks specific to the Kharwar. Such a combination of universal processes from the literature with local information ensures a culture-informed test battery (Brouwers & Van de Vijver, 2015). Differences between tasks from the same domain reside in the stimuli used to access those information processes.…”
Section: The Present Studymentioning
confidence: 99%